Exploring the effectiveness of combined mentalization‐based group therapy and dialectical behaviour therapy for inpatients with borderline personality disorder – A pilot study. (29th November 2016) - Edel, Marc‐Andreas; Raaff, Vanessa; Dimaggio, Giancarlo; Buchheim, Anna; Brüne, Martin
Abstract : Objectives: Borderline personality disorder (BPD) is characterized by emotional instability, interpersonal dysfunction, and other features that typically develop before a background of insecure attachment and traumatic experiences. Dialectical behaviour therapy (DBT) has proven highly effective in reducing self‐harm and improving emotion regulation, whereby problems concerning social cognition, which are also characteristic of BPD, may need additional approaches such as mentalization‐based treatment (MBT). Methods: Here, we examined, in a pilot study, the effectiveness of MBT given adjunct to DBT, compared to DBT alone, in an inpatient sample with BPD, whereby mentalization was measured using a novel cartoon‐based task. Results: Both treatments were highly effective in reducing symptom severity. The combination of DBT and MBT was superior in reducing fearful attachment and in improving affective mentalizing. Conclusions: Mentalization‐based treatment in combination with DBT may improve certain aspects of social cognitive skills and attachment security, as compared to DBT alone, although the exact mechanisms that led to these changes need to be studied further. Practitioner points: Clinical implications Dialectical behaviour therapy (DBT) can usefully be combined with mentalization‐based treatment (MBT). The combination of DBT and MBT reduces self‐harm more than DBT alone. DBT plus MBT may lead to a reduction in fearful attachment and improvement of affective mentalizing. Short‐term combinations of evidence‐based borderline treatments may enrich psychiatric inpatient care. Therefore, such approaches deserve further research. Limitations The treatment condition was therapeutically more intense than the control condition. The study lacked a follow‐up assessment. The impact of comorbid conditions on treatment response was not taken into account. Adherence to the manualized approach was not measured.